Leveraging Indigenous Architectural Patterns for Contextualized Learning: A Pedagogical Framework for Geometry in the Hena Puan Cultural Setting - Asria Ratau; Dwi Priyo Utomo; Joko Widodo; Yus Mochamad Cholily; Moh. Mahfud Effendi; Siti Inganah (CV. Bimbingan Belajar Assyfa, 2026)
The gap between abstract mathematical concepts and local cultural realities often hinders the effectiveness of students' geometric comprehension. This study aims to integrate the architectural wisdom of the traditional Baeleo Hena Puan house as a contextual pedagogical framework to strengthen geometric literacy. Through a qualitative exploratory descriptive approach, an in-depth visual analysis of the architectural structure was conducted to identify geometric concepts such as two-dimensional shapes (rectangles, triangles, trapezoids) and three-dimensional solids (rectangular and triangular prisms). The findings demonstrate that these architectural elements not only represent physical forms but also embody patterns of repetition and reflectional symmetry, reflecting complex mathematical activities in accordance with D’Ambrosio’s ethnomathematics theory. This research concludes that transforming architectural values into instructional materials serves as a strategic bridge to enhance students' cognitive engagement in meaningful mathematics learning. The proposed pedagogical framework provides an integrated learning model that enables educators to transform ethnomathematical data into instructional media relevant to 21st-century competency requirements. By incorporating traditional building designs into the formal curriculum, geometry instruction becomes more applicable while simultaneously functioning as a tool for preserving cultural identity within a modern educational setting. Implementing this framework is expected to facilitate a paradigm shift from formula-based learning to context-based and experiential-based learning.